Estudo da validade interna de um protocolo de terapia cognitivo-comportamental infantil para tratamento da sintomatologia depressiva e/ou ansiosa - Paiva, Camila Bosse (2018)
Mental disorders in childhood reach a prevalence of 13.4%, with 6.5% presenting with anxiety disorders and 2.6% with depressive disorder, the latter being the most prevalent in an isolated or comorbid form. The creation of programs to work these disorders in children becomes important for the non-progression of the symptoms in the later development. This study carried out a narrative review of the literature regarding the existing protocols for intervention with children based on cognitive-behavioral therapy. However, the main objective of this study was to evaluate the internal validity of the infant recycling therapy (TRI) protocol in reducing anxiety and / or depression symptoms in children aged 8 to 12 years. We also evaluated mental health problems among the participants and the intensity of cognitive distortions in the sample. The research consisted of a descriptive and explanatory study with a time series design. The TRI was applied in 22 children of both sexes with the purpose of comparing the symptoms of pre and post intervention children, as well as at the end of each stage of psychotherapy. The collection of symptomatic data was given by the application of SCARED and CDI, the cognitive distortions were monitored by the CATS questionnaire. Those responsible were assessed from the ASR. Of the participants who entered the study, 19 completed the protocol, which demonstrated good adherence to the treatment. The main symptomatology at admission was depression and the highest prevalence was in males. Participants presented a progressive reduction profile of both symptoms as well as negative automatic thoughts. Those responsible for the children presented clinical symptoms for internalizing problems. The data were analyzed by repeated measures ANOVA and to understand the differences of averages in each treatment step, Post Hoc analyzes were performed. The results suggest that the protocol contributed to the reduction of anxiety and depression significantly (p <0.005), as well as an improvement in the intensity of the cognitive distortions initially presented (p <0.005). The main symptom change occurred after the initial stage of the protocol, that is, the work with the emotions. These results suggest that TRI has proved to be a good clinical tool in the treatment of anxious and depressive symptoms in children and adolescents. Follow-up evaluations could indicate if these results were maintained over time, and this is a suggestion for future studies. In addition, we present the data from a conserved profile seen the absence of control group in this work, which could also be improved in other studies.